The role of networking alliances in information acquisition and its implications for new product performance - Soh, Pek-Hooi (Journal of Business Venturing, 2003)
The premise of Austrian economics on entrepreneurial discovery suggests that mutual knowledge about market participants defines who will acquire potential information about opportunities to bring future products into existence. Building upon this argument, this research investigates the role of networking alliances in information acquisition and its lagged effect on the new product performance of the firm. By using a longitudinal analysis, the study shows that a firm improves its new product performance as it increases the number of repeated partners and its centrality position relative to others in the technology collaboration network.